Ammonia borane–polyethylene oxide composite materials for solid hydrogen storage1. Issue 7 (21st February 2015) - Nathanson, A. S.; Ploszajski, A. R.; Billing, M.; Cook, J. P.; Jenkins, D. W. K.; Headen, T. F.; Kurban, Z.; Lovell, A.; Bennington, S. M.
<x xml:space="preserve">Abstract</x> Co-electrospinning ammonia borane (AB) and polyethylene oxide (PEO) has created a unique crystal phase that promotes faster hydrogen release from AB below its melting temperature with no incubation time.